Pentingnya Moderasi Beragama Dalam Dunia Pendidikan Di Indonesia - Dudun Najmudin; Randi Ahmad Rivandi; Ilham Pebrian (Prodi Pendidikan Agama Islam, Institut KH. Ahmad Sanusi Sukabumi, 2025)
Religious moderation in education has been considered to have an important role in shaping attitudes of tolerance and inclusiveness in a multicultural society. Solutions in maintaining social harmony and preventing conflicts due to extremism and intolerance have been found through a moderate understanding of religion. Education has been utilized as the main means to instill the values of religious moderation through curriculum, learning methods, and extracurricular activities designed to encourage interfaith interaction. A qualitative approach with a desk study method has been used in this research, with analysis conducted on various secondary sources such as books, scientific journals, and government policy documents. From the results of the research, it was found that appreciation of diversity is more prevalent among students who have been given an understanding of religious moderation, and higher levels of tolerance are also exhibited by them. However, some challenges remain, especially in the digital era, when the spread of inaccurate information is increasing and has the potential to trigger intolerance. Therefore, strengthening digital literacy is considered a necessary step so that information can be sorted out more critically. With the effective implementation of religious moderation-based education, national unity can be strengthened, and diversity can be used as a strength in building a more harmonious and civilized social life.